2023
DOI: 10.1136/bmjopen-2022-064870
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Organ Failure Assessment (SOFA) Score for predicting mortality in patients with sepsis in Vietnamese intensive care units: a multicentre, cross-sectional study

Abstract: Objectives To compare the accuracy of the Sequential Organ Failure Assessment (SOFA) and Acute Physiology and Chronic Health Evaluation II (APACHE II) Scores in predicting mortality among intensive care unit (ICU) patients with sepsis in a low-income and middle-income country. Design A multicentre, cross-sectional s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…However, recent studies have shown that the accuracy of SOFA score in predicting mortality may be limited. 42 43 44 …”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that the accuracy of SOFA score in predicting mortality may be limited. 42 43 44 …”
Section: Discussionmentioning
confidence: 99%
“…The utilization of both the SOFA and APACHE II scores effectively aided the prediction of mortality among ICU patients with sepsis. Nevertheless, owing to its superior discriminatory capability in forecasting ICU mortality, the preference leaned towards the SOFA score over the APACHE II score for mortality prediction [15].…”
Section: Significance Of Patient Triage In Icu Admissionsmentioning
confidence: 99%